Effect of Fungal Treatment on the Nutritive Value of Wheat Straw and its Use in the Diet of Dairy Cattle - Fazaeli, Hassan (2001)
Experiments were conducted to study the growth ability and potential of some Pleurotus fungi to biodegrade wheat straw and to determine the effect of fungal treatment on the nutritive value of straw and its use in the diet of dairy cow. The results showed that there is a potential application of the fungi on wheat straw. Among the six cultures of Pleurotus, P-41, P-21, P-60 and P-31 had a significantly (P<0.05) higher growth ability on wheat straw. Supplementation of wheat straw with 1 or 2% urea nitrogen did not enhance the colonisation and growth rate of the fungi. Fungal treatment decreased NDF and ADF, increased the CP and nutrient digestibility of wheat straw. However, the cultures P-30, P-41 and P-60 showed significantly (P<0.05) higher ability to degrade the cell wall components of the straw and improved the IVDMD, IVOMD and in sacco degradability. Treatment of wheat straw with Pleurotus (P-41) either before (FTWS) or after mushroom production (SPWS) resulted in a significantly (P<0.05) higher amount of nutrient intake (DMI, OMI and DOMI) when fed to bulls. The digestibility of DM and OM increased by more than 10% unit in the treated straw as compared to the untreated wheat straw. In comparison to the untreated straw, feeding fungal treated wheat straw resulted in a higher ruminal pH and ammonia nitrogen concentration that indicated an improvement in rumen fermentation. Improvement of nutritive value was higher in FTWS than the SPWS. In a feeding trial, four diets containing 0, 10, 20 and 30% fungal (P-41) treated wheat straw was fed to lactating cows. They showed similar intake of DM, OM, DOM, CP, TDN and NEL• All diets resulted in similar milk yield and milk composition, but the diets that contained 20 and 30% treated straw produced a significantly (P<0.05) higher body weight gain. However, the best animal performance and feed efficiency were obtained when the treated straw was included at 20% of the total diet or 40% of the roughage. When two diets containing 30% of untreated or fungal treated wheat straw were fed to late lactating cows, higher nutrient digestibility and intake of DM, OM, CP and ME were observed in the cows fed treated straw. There was 13% increase in FCM yield by cows fed treated straw. Daily body weight gain was 2.7 times in the treated straw diet as compared to the untreated straw group. Improvement in the animal performance reflects the availability of more digestible organic matter and energy from the wheat straw treated with the fungus.